Improved constraints on open-system processes in fossil reef corals by combined Th/U, Pa/U and Ra/Th dating: a case study from Aqaba, Jordan - Obert, Johanna Christina; Lippold, Jörg (Geochimica et cosmochimica acta, 2019)
Here we present 230Th/U, 231Pa/U as well as 226Ra/230Th isotope ratios from five fossil reef corals of Last Interglacial origin from the Gulf of Aqaba, Northern Red Sea. The results show clear evidence for open-system behaviour with strongly elevated δ234U values and U concentrations indicating post-depositional U addition. The combined application of all isotope systems enables us to better constrain the nature and timing of the open-system processes than only based on the 230Th/U data. Quantitative modelling of the diagenetic processes allowed us to reproduce the trends in the isotope ratios. Two of the five corals were probably affected by two separate phases of U addition with different δ234U values. The trends observed for two other corals can be explained by U addition followed by U loss. The fifth coral shows signs of both U gain and loss at the same time in the more recent past. The timing of the diagenetic processes is remarkably similar for the five corals and can be constrained to approx. 1 and 6 thousand years (ka) and 100 and 102ka after coral growth, respectively. Based on the modelling results, we suggest that conventional 231Pa/230Th ages provide the best estimate for the true age of four of the five corals, which range from 109.1 to 114.1ka. This implies a late Last Interglacial time of deposition. For the fifth coral, the most reliable age estimate is the conventional 230Th/U age of one of the subsamples (117.3ka), based on a concordia diagram for all subsamples. The timing of the modelled open-system processes suggests that the early event of U addition was associated with interaction of the corals with 234U-enriched seawater or saline groundwater. The later open-system event can be described as U redistribution within the coral reef, since some corals apparently lost U while others gained U. The timing of the second event is broadly consistent with the Bølling-Allerød interstadial, which was probably characterised by enhanced wetness in this typically hyper-arid region.
Available online 22 November 2018
Gesehen am 28.03.2019